Early development of treatment motivation predicts adherence and symptom reduction in an internet-based guided self-help program for binge eating disorder - Runge, Eik; Jensen, Esben Kjems; Mathiasen, Kim; Larsen, Pia Veldt; Hertz, Søren Peter Thygesen; Holmberg, Trine Theresa; Tarp, Kristine; Linnet, Jakob; Lichtenstein, Mia Beck (Frontiers in Psychiatry, 2022)
Objective: Lack of motivation is widely acknowledged as a major factor in treatment discontinuity and poor treatment outcomes in eating disorders. Treatment adherence is lower in internet-based treatment. The current study aimed to assess the relationship between treatment motivation and eating disorder outcomes in an internet-based therapist-guided intervention for Binge Eating Disorder (BED). Method: Adults (N = 153) with mild to moderate symptoms of BED participated in a 10-session internet-based treatment program. Between-session scores of “Readiness to change” and “Belief in change” were used to predict treatment completion and eating disorder symptom reduction (EDE-Q Global, BED-Q, and weekly number of binge eating episodes) at post-treatment. Results: Early measures of treatment motivation (regression slope from session 1-5) significantly predicted both treatment completion and post-treatment symptom reduction. “Belief in change” was the strongest predictor for completing treatment (OR = 2.18, 95%-CI: 1.06, 4.46) and reducing symptoms (EDE-Q Global: B = -0.53, p = 0.001; number of weekly binge-eating episodes: B = 0.81, p < 0.01). Discussion: The results indicated that patients entering online treatment for BED feel highly motivated. However, baseline treatment motivation could not significantly predict treatment completion, which contradicts previous research. The significant predictive ability of early measures of treatment motivation supports the clinical relevance of monitoring the development of early changes to tailor and optimize individual patient care. Further research is needed to examine treatment motivation, in regard to internet-based treatment for BED, with more validated measures.